Simulating the impact of Belt and Road initiative and other major developments in Myanmar on an ambassador felid, the clouded leopard, Neofelis nebulosa - Kaszta, Z; Cushman, SA; Htun, S; Naing, H; Burnham, D; Macdonald, DW (Springer Verlag, 2020)
Context: After decades of political and economic isolation, Myanmar is now the focus of large international investments, particularly from China, which raises questions of how to balance national development with safeguarding the Indo-Burma biodiversity hotspot.